Don't Wait, Communicate: Rural School Counselors and Disaster Mental Health. Issue 1 (9th June 2021) - Crumb, Loni; Appling, Brandee; Jones, Shenika
This study explored rural school counselors' experiences regarding their preparation and response to natural disasters. Using descriptive phenomenology, we examined the perspectives of 10 school counselors and identified four themes that captured their experiences: (a) the need for disaster mental health training, (b) the value of rural community collaboration, (c) the influence of multiple roles, and (d) personal reactions to disaster response. We provide implications and recommendations about expanding crisis training to include disaster mental health.